Extreme Events in Nature and Society - Albeverio, Sergio; Jentsch, Volker; Kantz, Holger; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Significant, and usually unwelcome, surprises, such as floods, financial crisis, epileptic seizures, or material rupture, are the topics of Extreme Events in Nature and Society. The book, authored by foremost experts in these fields, reveals unifying and distinguishing features of extreme events, including problems of understanding and modelling their origin, spatial and temporal extension, and potential impact. The chapters converge towards the difficult problem of anticipation: forecasting the event and proposing measures to moderate or prevent it. Extreme Events in Nature and Society will interest not only specialists, but also the general reader eager to learn how the multifaceted field of extreme events can be viewed as a coherent whole.
Extreme Events: Magic, Mysteries, and Challenges -- Extreme Events: Magic, Mysteries, and Challenges -- General Considerations -- Anticipating Extreme Events -- Mathematical Methods and Concepts for the Analysis of Extreme Events -- Dynamical Interpretation of Extreme Events: Predictability and Predictions -- Endogenous versus Exogenous Origins of Crises -- Scenarios -- Epilepsy: Extreme Events in the Human Brain -- Extreme Events in the Geological Past -- Wind and Precipitation Extremes in the Earth$1 (Bs Atmosphere -- Freak Ocean Waves and Refraction of Gaussian Seas -- Predicting the Lifetime of Steel -- Computer Simulations of Opinions and their Reactions to Extreme Events -- Networks of the Extreme: A Search for the Exceptional -- Prevention, Precaution, and Avoidance -- Risk Management and Physical Modelling for Mountainous Natural Hazards -- Prevention of Surprise -- Disasters as Extreme Events and the Importance of Network Interactions for Disaster Response Management.s
Keywords: Physics; Meteorology; Applied mathematics; Engineering mathematics; Statistical physics; Dynamical systems; Environmental sciences; Economic theory; Physics; Statistical Physics, Dynamical Systems and Complexity; Applications of Mathematics; Meteorology; Economic Theory/Quantitative Economics/Mathematical Methods; Math. Appl. in Environmental Science; Physics, general; Electronic books